GRAVIMETRIC AND ELECTROCHEMICAL TEST OF ETLINGERA ELATIOR INFLORESCENCE EXTRACT AS GREEN CORROSION INHIBITOR (Jurnal Teknologi (Sciences & Engineering), 2022)
At present, organic corrosion inhibitors which are commonly used such as silicate and phosphate have a high level of toxicity. It has prompted the search for green corrosion inhibitors because of its eco-friendly properties and has a lower level of toxicity. Therefore, this study has been conducted to investigate the inhibition efficiency (IE%) and corrosion rate of mild steel in 0.5 M HCl acidic medium. The data obtained through weight loss and the electrochemical method at various concentrations and temperatures. The surface morphologies was observed using Scanning Electron Microscope (SEM). Different experimental conditions were also used such as electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization curves (PPC). EIS findings revealed that the addition of studied inhibitors prevented the degradation of mild steel in HCl solution, hence leading to a high value of polarization resistance compared to the blank solution. Besides that, the PPC results suggested that the tested samples had a mixed-type effect which decreased the anodic and cathodic corrosion reactions. Surface characterization by SEM illustrated a notable decrease in surface roughness of mild steel after the addition of inhibitors. Outcomes from the present study indicates that the Etlingera Elatior inflorescence extract acts as a good corrosion inhibitor for mild steel sample in HCl solution with IE% value above 93.63 %. Formation of the protective layer becomes weaker as the temperature raises.